Housing Finance Policy in Emerging Markets - Chiquier, Loic (World Bank, 2012)
This report documented the importance of housing in the economy while at the same time providing governments with guidelines on how best to design policy to create efficient housing markets. The purpose of this book is to provide fact-based information and guidance to policy makers concerned with housing finance in emerging markets. An overarching goal is to improve the understanding of the importance of housing finance to the economy. This includes covering the prerequisites for an effective housing finance system together with the main characteristics of such a system. The book continues by laying out some of the policy alternatives and models of housing finance (products, infrastructure, risk management, regulations, and funding). In line with the priorities of many governments, the book is focused on solutions; in particular the role of government in contributing to the growth of housing finance and in increasing access to housing finance for lower and informal income households. The way taken to achieve these objectives is of the essence: they cannot be achieved, at least in a sustainable manner, by involving the creation of undue additional risks for the financial sector or eventually unbearable fiscal liabilities.